Estrat??gias biomec??nicas e de controle motor adotadas por indiv??duos saud??veis durante a execu????o de um exerc??cio de flex??o e extens??o do tronco no Cadillac segundo o m??todo Pilates - Costa, Th??o Abatipietro (2010)
The Pilates Method, exercise system developed by German Joseph Hubertus Pilates (1880-1967) focuses on the work of stretching and strengthening exercises to stabilize the abdominal and lumbar region, one of the main features of the Pilates method is the use of specific equipment that has the distinction of offering resistance through springs (elastic load), and despite its growing popularity worldwide and observation of their benefits in clinical practice, a literature review on the subject reveals that there are few published scientific studies. Another problem is related to the scientific validity of the method is the lack of studies with an approach based on biomechanics and motor control. Therefore the aim of our study is to describe, in terms of kinematic and electromyographic, the exercise of trunk flexion and extension performed on the equipment according to Pilates Cadillac and correlate the imposition of different conditions C1 (without elastic resistance of the load), C2 (resistance to elastic load) and C3 (assistance elastic load) and electromyographic activity the anterior deltoid, posterior deltoid, rectus abdominis, external oblique and internal oblique during the three phases of movement (one way, maintenance of posture and return to starting position). Nine volunteers participated in this study with 25 + - 3.8 years, 1.62 + 53.5 + -0.4 I - 4.6 kg. The volunteers were instructed to make fifteen repetitions of the task in three different conditions in the Cadillac unit. The movements of the shoulder, upper trunk, middle trunk and lower trunk were reconstructed using an optical three-dimensional analysis of the movements (Optotrak 3020) and electromyographic activity of major muscles were recorded using surface electrodes (Delsys Inc.) A two-way ANOVA revealed that there is an orientation of the upper trunk during the stages and conditions, (p = 0.01), not showing the same for the middle and lower trunk. In the peak velocity in which it was calculated separately for the three segments, the ANOVA revealed p <0.02 only for the upper trunk and middle trunk. The condition imposed in the exercise did not show significant results for both segments at peak speed. At the time of movement in which we calculated the time of each stage a one-way ANOVA (F (1,80) = 152.39, p <0.00) revealed that individuals were less time on target and that the statement of the task's time three phases should be close to 4 seconds. The rate of symmetry that is formed by acceleration and deceleration of the back and forth a two-way ANOVA revealed the effect of phases of movement (F (2,53) = 09.06, p = 0.00), not showing the same to the conditions and segments.